Development of Indonesian Association of People with Disabilities (PPDI) Volunteers Based on Digital Applications to Increase Deaf Interaction - Hardiyanto, Sigit; Dalimunthe, Rehana Salsabila; Lubis, Chalisa Audia; Daulay , Syahru Ramadhan (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background:  Effective communication is essential for everyone, but it can be especially difficult for those who are deaf or hard of hearing. This can lead to isolation and hinder their ability to express themselves. Unfortunately, many people, including volunteers from PPDI North Sumatra, lack sign language skills, creating a communication barrier with the deaf community. Contribution: This activity aims to develop and assist Regional Representative Council PPDI North Sumatra volunteers to increase interaction with the deaf at Regional Representative Council PPDI North Sumatra Method: PPDI volunteers participated in program socialization, learned PIKU application features, and received training on its use. Results: The PIKU program yielded positive outcomes. Volunteer participation was enthusiastic, and interaction with the deaf community increased. The app's free accessibility, user-friendly interface, and clear visuals facilitated communication. Conclusion: The PIKU program, with its communication-assistive technology, effectively improved interaction between PPDI volunteers and the deaf community in North Sumatra. This highlights the potential of technology to break down communication barriers and foster inclusivity